2012
DOI: 10.1080/14748460.2012.659057
|View full text |Cite
|
Sign up to set email alerts
|

The effect of active teaching and subject content coverage on students' achievement: evidence from primary schools in Kenya

Abstract: There is a growing public concern in Kenya over the persistent gap between those schools that are consistently ranked at the top and those ranked at the bottom of the annual Kenya Certificate of Primary Education (KCPE) examination league tables. This has raised the issue of inequality in educational opportunity. Our primary concern in this paper is to understand some of the classroom-school factors that may explain the persistent differences in achievement between the top and bottom schools. We focus on time-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…While not ubiquitous in the literature, gain‐score formulations of the achievement regression have been used in recent work (e.g., Jackson, ; Kinsler, ; Koedel, Leatherman, & Parson, ; Lefgren & Sims, ; Oketch et al., ; Subedi, Swan, & Hynes, ). The motivation for using the gain score rather than the lag score varies.…”
Section: Framework and Backgroundmentioning
confidence: 99%
“…While not ubiquitous in the literature, gain‐score formulations of the achievement regression have been used in recent work (e.g., Jackson, ; Kinsler, ; Koedel, Leatherman, & Parson, ; Lefgren & Sims, ; Oketch et al., ; Subedi, Swan, & Hynes, ). The motivation for using the gain score rather than the lag score varies.…”
Section: Framework and Backgroundmentioning
confidence: 99%
“…OTL is a well‐established concept that considers learning as a function of the time students are exposed to the intended curriculum (Wilson et al, 2016). Some authors simply defined it as time‐on‐task and exposure to subject matter (Liu et al, 2015; Oketch et al, 2012; Wilson et al, 2016), whereas others considered resources and variety in teaching, grouping and learning activities (Azigwe, 2016; Heafner & Fitchett, 2015). Despite the different interpretations, it is a well‐established concept that recognises the importance of providing students with equitable access to the required content.…”
Section: Resultsmentioning
confidence: 99%
“…Concerning the final sub-category, material resources, Morningstar et al, (2015) noticed that classrooms where learning technologies were available and used by teachers had the greatest potential for learner participation (behavioural outcomes). Similarly, Oketch et al, (2012) found that the availability of non-basic learning material (e.g., visual aids, charts), in addition to smaller pupil-teacher ratios, positively affected cognitive outcomes.…”
Section: Resources and Opportunity To Learnmentioning
confidence: 89%
“…While not ubiquitous in the literature, gain score formulations of the achievement regression are still used in recent work (for example, Jackson 2009, Koedel et al 2012, Kinsler 2011, Lefgren & Sims 2012, Oketch et al 2012, Subedi et al, 2011. The motivation for using the gain score rather than the lag score specification often varies.…”
mentioning
confidence: 99%